Modelling and Nonlinear Dynamics of Third-Order Thermomechanically Coupled Laminated Plates - Saetta, Eduardo; Rega, Giuseppe (NTU "KhPI", 2016)
Thermomechanically coupled, geometrically nonlinear, laminated plates are addressed through a unified 2D formulation that integrates mechanical and thermal aspects and consistently accounts for cubic variations along the thickness of both in-plane displacement components and temperature. It allows to address a variety of thermal boundary conditions on the plate upper and lower surfaces. Minimal dimension reduction of the problem is pursued for symmetric cross-ply laminates. A numerical case study provides hints on the potential of the reduced model for the analysis of thermomechanical coupling effects on the system nonlinear dynamics.
Keywords: thermomechanical modelling; laminated plates; nonlinear dynamics